Glucosylceramide synthase inhibition in combination with aripiprazole sensitizes hepatocellular cancer cells to sorafenib and doxorubicin - Jennemann, Richard; Volz, Martina; Frias Soler, Roberto Carlos; Schulze, Almut; Richter, Karsten; Kaden, Sylvia; Sandhoff, Roger (International journal of molecular sciences, 2024)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer deaths due to its late diagnosis and restricted therapeutic options. Therefore, the search for appropriate alternatives to commonly applied therapies remains an area of high clinical need. Here we investigated the therapeutic potential of the glucosylceramide synthase (GCS) inhibitor Genz-123346 and the cationic amphiphilic drug aripiprazole on the inhibition of Huh7 and Hepa 1-6 hepatocellular cancer cell and tumor microsphere growth. Single and combinatorial treatments with both drugs at 5 µM concentration led to efficient cell cycle arrest, reduced expression of cyclins A and E, increased lipid storage in lysosomal compartments, accompanied by increased uptake of lysotracker, and elevated expression of the autophagy marker Lc3 II. Both drugs affected mitochondrial function, indicated by altered mitotracker uptake and impaired mitochondrial respiration. Aripiprazole in monotherapy, or even more pronounced in combination with Genz, also potentiated the effect of the cytostatic drugs sorafenib and doxorubicin on tumor cell- and tumor spheroid-growth inhibition. Targeting GCS with Genz with the parallel application of cationic amphiphilic drugs such as aripiprazole in combination with cytostatic drugs may thus represent a potent therapeutic approach in the treatment of HCC and potentially other cancer types.